2021
DOI: 10.2478/ijame-2021-0003
|View full text |Cite
|
Sign up to set email alerts
|

Computer Analysis of Dynamic Reliability of Some Concrete Beam Structure Exhibiting Random Damping

Abstract: An efficiency of the generalized tenth order stochastic perturbation technique in determination of the basic probabilistic characteristics of up to the fourth order of dynamic response of Euler-Bernoulli beams with Gaussian uncertain damping is verified in this work. This is done on civil engineering application of a two-bay reinforced concrete beam using the Stochastic Finite Element Method implementation and its contrast with traditional Monte-Carlo simulation based Finite Element Method study and also with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Probabilistic analysis has been performed with the Stochastic Perturbation Technique (SPT), and independently using Monte-Carlo simulations (MCS) and semi-analytical method (SAM) also [7], [8]. The results obtained by SPT are marked with asterisk, these coming from the MCS -with a cross, while these obtained by SAM -with a diagonal box.…”
Section: Probabilistic Analysismentioning
confidence: 99%
“…Probabilistic analysis has been performed with the Stochastic Perturbation Technique (SPT), and independently using Monte-Carlo simulations (MCS) and semi-analytical method (SAM) also [7], [8]. The results obtained by SPT are marked with asterisk, these coming from the MCS -with a cross, while these obtained by SAM -with a diagonal box.…”
Section: Probabilistic Analysismentioning
confidence: 99%
“…When designing a structure with respect to robustness, it must also be taken into consideration that progressive collapses caused by extreme events are low-probability high-consequence phenomena [1]. In order to be able to accurately predict the structural response, it is important to study the progressive collapse behavior using a probabilistic approach, as it has been found that there is a significant influence of many uncertainties on the structural behavior, e.g., randomness from material properties, which is neglected by most existing studies [30][31][32][33][34][35][36][37][38][39][40][41][42]. However, in the three widely used approaches in relation to the quantification of the structural robustness, i.e., deterministic-based method, probabilisticbased method, and risk-based method [30,43,44], both the probabilistic-based method and the risk-based method require a reliability analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the three widely used approaches in relation to the quantification of the structural robustness, i.e., deterministic-based method, probabilisticbased method, and risk-based method [30,43,44], both the probabilistic-based method and the risk-based method require a reliability analysis. Several approaches can be adopted in a probabilistic analysis in combination with the finite element method [35,41,42,45], such as the Monte Carlo simulation [42] and the Latin Hypercube sampling technique [45]. Moreover, considering that the EBM is an approximate approach, the quantitative assessment of the model uncertainty associated to the EBM becomes important when the EBM is applied to quantify the reliability or robustness of a RC building structure following a sudden column removal scenario.…”
Section: Introductionmentioning
confidence: 99%